Missed nursing care perceived by mothers of hospitalized pediatric patients - González-Sánchez, Ada Lizette (Universidad de Sonora, 2020)
Introduction: Missed nursing care is defined as the care required by the patient that is omitted (partially or totally) or significantly delayed. In the pediatric population, it is relevant to identify the missing care given the vulnerability of children, who may not be able to express or demand the necessary attention. Objective: Identify the missed nursing care and its relationship with the reasons perceived by the mothers. Methodology: Descriptive correlational study. One hundred sixty two (162) mothers of pediatric patients from a public hospital participated. Data were collected with the MISSCARE instrument; for the analysis, descriptive and inferential statistics were used. Results: Main misscare situations are planning of discharge and patient education, followed by basic care such as helping, or carrying, mouth and hands washing (82.1%), checking that the food is at the proper temperature (62.1%) and bringing the food to the patient as well as check the diet before they eat it (61.1%). Lack of enough human resources is the main reason why care is missed. Additionally, unexpected increase in the amount of patients and/or workload (47%) and emergency situations that demand more attention and, thus, generate insufficient time to attend other patients (34.5%) stood out. Conclusions: Missed care was identified in the hospitalized pediatric patients and is mainly attributed to lack of human resources. This information shall be considered as relevant by the managers in order to strengthen nursing care in pediatric population.